Dermoscopic spectrum of mycosis fungoides: a retrospective observational study by the International Dermoscopy Society. (28th March 2022) - Errichetti, E.; Apalla, Z.; Geller, S.; Sławińska, M.; Kyrgidis, A.; Kaminska‐Winciorek, G.; Jurakic Toncic, R.; Bobos, M.; Rados, J.; Ledic Drvar, D.; Ceovic, R.; Akay, B. N.; et al.
Abstract: Background: The dermoscopic features of classic patch stage mycosis fungoides (MF) have been described, but data on plaque and tumoral stage as well as rarer MF subtypes is limited. Objective: To evaluate dermoscopic morphology and dermoscopic‐pathological correlations of classic MF stages and investigate dermoscopic features of MF variants. Methods: Patients with histopathologically confirmed lesions of classic MF (patch, plaque and tumoral stage) or folliculotropic, erythrodermic and poikilodermatous MF were included. Standardized evaluation of dermoscopic pictures of the included MF variants and comparative analysis and dermoscopic‐pathological correlation assessment of different stages of classic MF were performed. Results: A total of 118 instances were included (75 classic MF, 26 folliculotropic MF, 9 erythrodermic MF and 8 poikilodermatous MF). Linear/linear‐curved vessels and white scales in the skin furrows were significantly associated with patch‐stage MF, while clustered dotted vessels were related to plaque‐stage MF and peripheral linear vessels with branches, ulceration and red globules separated by white lines to tumour‐stage MF. Moreover, patchy white scales were significantly more common in patches and plaques compared to tumours, whereas focal bright white structureless areas were related to plaque and tumoral stage. Vessels histopathologically corresponded to dilated vascular structures in the dermis, orange structureless areas to either dermal hemosiderin (patch/plaque stage) or dense cellular infiltration (tumours), bright white lines/structureless areas to dermal fibrosis and ulceration to loss of epidermis. The main dermoscopic findings of folliculotropic MF were lack of hairs, dilated follicles and follicular plugs, while erythrodermic MF was mainly characterized by linear/dotted vessels, patchy white scales and focal orange structureless areas and poikilodermatous MF by focal white and brown structureless areas, white patchy scales and brown reticular lines. Conclusion: Dermoscopy may allow a more precise characterization of classic MF and reveal clues suggestive of the main MF variants.